2014
DOI: 10.4028/www.scientific.net/amm.699.204
|View full text |Cite
|
Sign up to set email alerts
|

Water Uptake Behavior of Lignin Modified Starch Film

Abstract: A biodegradable urea crosslinked starch film was prepared. To improve the water resistance, the urea crosslinked starch system was reinforced with 5%, 10%, and 15% lignin. The prepared films were immersed in distilled water at three different temperatures, 25°C, 35°C and 45°C to study the behavior of water uptake. The addition of lignin effectively decreases water uptake as proven by lower water uptake equilibrium. Diffusion coefficient was calculated from the kinetic water uptake profile using the slope metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…To investigate the water uptake behavior, the produced films were placed in distilled water at three temperatures, 25, 35 and 45 °C. Lower water uptake equilibrium confirmed that the addition of lignin decreased water uptake effectively due to the hydrophobicity of lignin [90].…”
Section: Application Of Lignin In Bioplasticsmentioning
confidence: 99%
“…To investigate the water uptake behavior, the produced films were placed in distilled water at three temperatures, 25, 35 and 45 °C. Lower water uptake equilibrium confirmed that the addition of lignin decreased water uptake effectively due to the hydrophobicity of lignin [90].…”
Section: Application Of Lignin In Bioplasticsmentioning
confidence: 99%
“…A large majority of the starch-lignin studies have reported an increase in water resistance of the composite materials compared to those made of starch alone. 161,162 Baumberger and co-workers have made a significant contribution to the fundamental understanding, processing, and applications of lignin-starch composites and blends. 163 One of the key questions has been the compatibility of lignin in a starch matrix.…”
Section: Lignin-based Nanocompositesmentioning
confidence: 99%
“…12 describes first time the theoretical framework about dual implication of lignin i.e., concomitantly reducing the biodegradability and release of ureanitrogen. Lignin due to hydrophobic character, could minimize effectively the wettability of hydrophilic starch in lignin-starch composite films [28]. Urea release requires that films absorb water first and later swells through relaxation of polymer network.…”
Section: 7mentioning
confidence: 99%
“…Urea release requires that films absorb water first and later swells through relaxation of polymer network. The swelling of polymer network reduces more with increase of lignin [28]. But low biodegradability and antioxidant properties of lignin [29] contributes to protect oxidative degradation of starch.…”
Section: 7mentioning
confidence: 99%